Daily Life of the Black Sea Province on the Pages of the Newspaper «North Caucasus» (Proceedings of Southern Federal University. Philology, 2020)
The article analyzes the periodicals of the Black Sea province at the turn of the XIX-XX centuries, it considers the features of the editorial policy of the newspaper «North Caucasus» in highlighting the daily life of the Black Sea province.Key words: Black Sea province, periodicals, F.S. Leontovich, Novorossiysk leaflet, Black Sea coast, North Caucasus, editorial policy, everyday life.DOI 10.18522/1995-0640-2020-1-227-232